Metabolic Dyslipidemia and Risk of Coronary Heart Disease in 28,318 Adults With Diabetes Mellitus and Low-Density Lipoprotein Cholesterol <100 mg/dl - Rana, Jamal S.; Liu, Jennifer Y.; Moffet, Howard H.; Solomon, Matthew D.; Go, Alan S.; Jaffe, Marc G.; Karter, Andrew J. (The American journal of cardiology, 2015)
The risk of future coronary heart disease (CHD) in subjects with diabetes and “metabolic dyslipidemia” (high triglyceride [TGs] and low high-density cholesterol levels) remains a matter of concern. Little is known regarding the risk of CHD for this phenotype with low-density lipoprotein cholesterol (LDL-C) levels <100 mg/dl. We analyzed a diabetes cohort of 28,318 members (aged 30 to 90 years) of Kaiser Permanente Northern California during 2002 to 2011 (192,356 person-years [p-y] follow-up), with LDL-C levels <100 mg/dl and without known CHD. We compared the incidence and hazard ratios (HRs) for CHD events in groups using Cox models: normal high-density lipoprotein (HDL) and TG (reference; n = 7,278, 25.7%); normal HDL and high TG (≥150 mg/dl; n = 4,484,15.8%); low HDL (≤50 mg/dl for women and ≤40 mg/dl for men) and normal TG (n = 4,048, 14.3%); low HDL and high TG (metabolic dyslipidemia; n = 12,508, 44%). Patients with metabolic dyslipidemia had the highest age-adjusted CHD events/1,000 p-y (12.7/1,000 p-y and 19.0/1,000 p-y for women and men, respectively). After multivariate adjustment for age, gender, ethnicity, hypertension, smoking, statin use, duration of diabetes, and hemoglobin A1c, we observed an increased CHD risk in women (HR 1.35, 95% confidence interval 1.14 to 1.60) and men (HR 1.62, 95% confidence interval 1.43 to 1.83) with metabolic dyslipidemia compared to those with normal HDL and TG. Even in subjects with an LDL-C <100 mg/dl, presence of metabolic dyslipidemia in adults with diabetes is associated with an increased risk of CHD. In conclusion, effective CHD prevention strategies are needed for adults with diabetes and metabolic dyslipidemia.